Pengaruh Suplementasi Jus Pisang Raja (Musa paradisiaca var sapientum) Terhadap Kinerja Olahraga - Yesticia Erwinda Josef; Hayati (LPPM Universitas PGRI Adi Buana, 2019)
Banana has effect in improving the level of sport performance . Many people consume it because it is easy to found and also cheap. The aim of the study is to find out whether Raja banana juice can enhance the sport performance by improving the endurance level? Sample of the study were 36 male students in Class X of TPm in SMKN 3 Buduran, Sidoarjo. Sample was randomized chosen which then classified into 2 groups (each group consisted of 18 students). Design used in the study was Randomized Control Group Pre-test Post-test design. According to the data analysis it was resulted that tcount of Raja banana juice was 14.18 while in both ttable and N=18 in significant value of 5% was 2.110 that can be concluded that tcount > ttable. In contrast, tcount of 17.27 was resulted for water (aquadest) liquid and similarly, in both ttable in significant value of 5% was 2.110 . Thus, alternative hypothesis showing that there is a relationship in Raja banana juice providing on the performance of Class X students of TPm in SMKN 3 Buduran Sidoarjo in performing 2.4 km run was valid. The Result of the Research is Significant that